IMMUNOHISTOCHEMICAL LOCALIZATION OF CONTRACTILE PROTEINS IN LIMULUS STRIATED MUSCLE - Levine, Rhea J. C. (The Rockefeller University Press, 1972)
Limulus paramyosin and myosin were localized in the A bands of glycerinated Limulus striated muscle by the indirect horseradish peroxidase-labeled antibody and direct and indirect fluorescent antibody techniques. Localization of each protein in the A band varied with sarcomere length. Antiparamyosin was bound at the lateral margins of the A bands in long (∼ 10.0 µ) and intermediate (∼ 7.0 µ) length sarcomeres, and also in a thin line in the central A bands of sarcomeres, 7.0–∼6.0 µ. Antiparamyosin stained the entire A bands of short sarcomeres (<6.0). Conversely, antimyosin stained the entire A bands of long sarcomeres, showed decreased intensity of central A band staining except for a thin medial line in intermediate length sarcomeres, and was bound only in the lateral A bands of short sarcomeres. These results are consistent with a model in which paramyosin comprises the core of the thick filament and myosin forms a cortex. Differential staining observed using antiparamyosin and antimyosin at various sarcomere lengths and changes in A band lengths reflect the extent of thick-thin filament interaction and conformational change in the thick filament during sarcomeric shortening.